Coordenação de Containers no Kubernetes: Uma Abordagem Baseada em Serviço - Netto, Hylson Vescovi; Oliveira, Caio Pereira; Luiz, Aldelir Fernando; Lung, Lau Cheuk; Rech, Luciana de Oliveira; Júnior, José Roque Betiol (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2017)
The cloud computing paradigm have been modified. One of the most impacting changes is the usage of system level virtualization, for a better infrastructure management. The creation of Kubernetes, a containers management system, by the Cloud Native Computing Foundation (CNCF) express the efforts to guide the changes in a standard manner. Kubernetes can replicate containers, but not the state of the applications hosted in the containers. This paper presents an architecture for replicating state in containers providing coordination as a service, with a light and simple coupling to the application. Some experiments analyse the behavior of applications which observe eventual and strong consistency when reading data. The results shown that the proposal is feasible.